نمذجة جزيئية لمشتقات Benzimidazole بإستعمال QSAR واإللتحام الجزيئي - عطية, دويمي; رمضان, شعباني; أحمد, اليمان (My University, 2022)
يف هذه الدراسة ، مت تطوير منوذجني QSAR لـــ 23 مشتقا للـــ Benzimidazoles لديهم نشاط بيولوجي ضد مرض الزهامير بإستخدام طريقة اإلحندار اخلطي )MLR .)مت حساب الواصفات املستخدمة بوسطة طريقة نظرية الكثافة ،Hyperchem برنامج وكذلك، Gaussian09 لربنامح( DFT/B3LYP/ 6-31G d'( الوظيفية swissADME ......ومت تقييم قدرة التنبؤ لنماذج QSAR بواسطة طريقة )LOO )وقد لوحظ وجود إرتباط بني قيم النشاط التجرييب واملتوقع , مما يدل على اجلودة العالية لنماذج QSAR املتحصل عليها. وكان اهلدف الثاين لدراستنا هو إستخدام طرق النمذجة اجلزيئية، وحتديدا اإللتحام اجلزيئي لدراسة األمناط احملتملة للتفاعل بني إنزميي AChE و BuChE و مشتقات Benzimidazole. وأخريا مت التنبؤ باحلركية الدوائية للمركبات أي تأثري الكائن احلي على الدواء خالل حركته داخل اجلسم عرب أربع مراحل تعرف بـ ADME ،و مت ذلك عن طريق دراسة خاصية التشبه باألدوية druglikeness و كذلك التنبؤ بإحتمالية اإلمتصاص املعوي HIA و النفادية عرب احلاجز الدموي الدماغي )BBB.(In this study, two QSAR models were developed using the MLR method for 23 benzimidazoles with activity anti-Alzheimer. The descriptors used were calculated by DFT/ B3LYP/6-31G' method in Gaussian09 program, Hyperchem, swissADME ....... The prediction ability of these QSAR models were evaluated by (LOO) method. A correlation was observed between the experimental and predicted activity values, which indicates the high quality of QSAR models obtained. The second objective of our study was to use molecular modeling (docking molecular), to study the possible types of interaction between AChE and BuChE enzymes and 23 benzimidazole derivatives. Finally, the pharmacokinetics of the compounds were predicted, i.e. the effect of the organism on the drug during its movement inside the body through 4 stages known as ADME, and this was done by studying the drug-likeness property, as well as predicting the probability of intestinal absorption (HIA) and Permeability across the blood-brain barrier (BBB).
مذكرة ماستر كيمياء
Keywords: اإللتحام اجلزيئي ، مرض الزهامير، ADME ، QSAR ، خاصية التشبه باألدوية ، Benzimidazole.; molecular docking , Anti-Alzheimer , ADME QSAR , drug-likeness property , Benzimidazole.